The Implementation of Deep Learning as an Effort to Realize Transformative Education in Elementary School - Noptario; Alia Latifah; M. Ferry Irawan; Abd Razak Zakaria (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2025)
Twenty-first century education demands learning approaches that cultivate students’ critical, reflective, and adaptive thinking skills to respond to rapid changes in society. Although deep learning has been widely promoted as a strategy to support transformative education, many elementary schools in Indonesia still rely on conventional, teacher-centered methods, leading to limited student engagement, shallow understanding, and minimal opportunities for reflection and inquiry. This gap between the expected transformative learning practices and the realities of classroom implementation provides an opportunity to investigate how deep learning can be applied effectively at the primary level. This study aimed to explore the implementation of a deep learning system in elementary education and examine its contribution to realizing transformative learning. The research employed a qualitative descriptive design with data collected through interviews, observations, and documentation at SD Negeri 46 Pagaralam, South Sumatra Province. The participants consisted of teachers and students directly involved in deep learning practices. The findings show that deep learning was implemented through five strategies. These strategies foster active engagement, higher-order thinking, and the development of human values such as empathy, ethics, and social responsibility. The study concludes that deep learning not only enhances the quality of the learning process but also contributes significantly to students’ cognitive and character transformation. The implications highlight the importance of teacher training, flexible curriculum, and technological support to sustain deep learning implementation in elementary schools.